Early and Late Support Measured over Various Distances: The Covered versus Open Part of the Orchestra Pit. Issue 4 (December 2013) - Wenmaekers, R.H.C.; Hak, C.C.J.M.
The Early and Late Support parameters (STearly and STlate ) are used to describe acoustic conditions on stage. Recently, extended Support parameters have been introduced which can be measured at various distances: STearly, d and STlate, d . This way, the amount of reflected sound energy can be studied for sound paths with distances between source and receiver larger than 1 meter. Occasionally, Early and Late Support are also used to investigate orchestra pits. Using the extended Support parameters, the mutual support from reflections between the positions in the open and covered part of the orchestra pit has been investigated. It is found that, when plotting STearly, d as a function of distance, three different trends are found each having a distinctive shape for different types of source and receiver positions: both positions in the open part; both positions in the covered part; and just one of both positions in the open or covered part. When comparing the different trends, a large increase is found in early reflected sound energy when either source or receiver or both are in the covered part of the pit. In the covered part, at 1 meter distance the level of reflected sound can even be in the same order of magnitude as the direct sound. When considering the late reflected sound energy it was found that STlate, d was not dependent on the source to receiver distance and less difference was found between the open and covered part of the orchestra pit.